Rethinking play and pedagogy in early childhood education : concepts, contexts and cultures - Rogers, Sue. (London ; New York : Routledge, 2011)
Addresses contemporary issues surrounding play and pedagogy including: the application of critical and socio-cultural analyses to play in early childhood; renewed interest in the aesthetic, creative and affective dimensions of play in early childhood education; and, diversity, identity and social justice within early childhood settings
Includes bibliographical references and index.
Keywords: Play; Early childhood education; Critical pedagogy